Skills Conditions Towards Sarawak 2030: Perspectives From Policy Actors - Mohamad Ashari, Noratikah (2024)
The primary purpose of this study is to explain the plausible futures of the Sarawak public sector’s skills conditions through policy actors’ perspectives towards 2030. The study seeks to a) describe the shared meaning of the current skills conditions for the Sarawak public sector, b) analyse the plausible futures on the skills conditions towards Sarawak 2030; and c) construct the plausible futures of skills conditions for Sarawak 2030.